2022
DOI: 10.1021/acs.est.1c07422
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Preconception Couples to Legacy and Emerging Per- and Polyfluoroalkyl Substances: Variations Within and Between Couples

Abstract: Exploration of the exposure of preconception couples to per- and polyfluoroalkyl substances (PFAS), as well as the most important influencing factors, promotes the understanding of the joint effects of parental exposure on reproductive health. In the present study, a total of 938 preconception couples recruited through the Shanghai Birth Cohort were investigated for the variations of PFAS exposure and contributing factors within and between couples. While linear perfluorooctanoic acid (n-PFOA, median 20.4 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…concentrations among pregnant women and children, 13 to date, only one Chinese study evaluated the predictors of PFAS concentrations among preconception couples. 14 The study found that PFAS concentrations were weakly to moderately correlated within couples, and males, in general, had higher PFAS concentrations than females. The study also examined household factors in relation to couples' PFAS concentrations but did not examine other relevant factors such as diet.…”
Section: ■ Introductionmentioning
confidence: 83%
“…concentrations among pregnant women and children, 13 to date, only one Chinese study evaluated the predictors of PFAS concentrations among preconception couples. 14 The study found that PFAS concentrations were weakly to moderately correlated within couples, and males, in general, had higher PFAS concentrations than females. The study also examined household factors in relation to couples' PFAS concentrations but did not examine other relevant factors such as diet.…”
Section: ■ Introductionmentioning
confidence: 83%
“…Technical details of the detection of these two diPAPs and other legacy PFAS were described previously. 23 The limit of detections (LODs) of 6:2 and 8:2 diPAPs were determined to be 0.03 and 0.07 ng/mL, respectively. However, in the present study, while the detection rate of 6:2 diPAP was >90%, 8:2 diPAP was undetectable.…”
Section: ■ Methodsmentioning
confidence: 97%
“…The reference standards of 6:2 and 8:2 diPAPs and isotopically labeled 13 C-6:2 diPAP were purchased from Wellington Laboratories (Guelph, Ontario, Canada). The sample treatments for 6:2 and 8:2 diPAPs followed the procedures described previously. Briefly, plasma samples (100 μL each) were spiked with isotopically labeled surrogate standards and then loaded onto the Captiva EMR-Lipid 96-well plates (1 mL, Agilent Technologies, USA). Solid-phase extraction was conducted on a Biotage Extrahera automation system (Biotage, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the general population, lower concentrations in females than in males have been found for several PFASs. 29,38 However, the sex differences may change in the old age group. A previous study 39 reported that the serum concentration of PFOS and PFOA in menopausal females over 51 years of age was higher than that in females between the ages of 20 and 50 years; besides, no difference was found in the serum levels of PFASs between males and postmenopausal females.…”
Section: ■ Introductionmentioning
confidence: 99%